2005
DOI: 10.1038/sj.jcbfm.9600097
|View full text |Cite
|
Sign up to set email alerts
|

Role of Arginine Vasopressin V1 and V2 Receptors for Brain Damage After Transient Focal Cerebral Ischemia

Abstract: Brain edema formation is one of the most important mechanisms responsible for brain damage after ischemic stroke. Despite considerable efforts, no specific therapy is available yet. Arginine vasopressin (AVP) regulates cerebral water homeostasis and has been involved in brain edema formation. In the current study, we investigated the role of AVP V 1 and V 2 receptors on brain damage, brain edema formation, and functional outcome after transient focal cerebral ischemia, a condition comparable with that of strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(77 citation statements)
references
References 35 publications
2
75
0
Order By: Relevance
“…These clinical observations are consistent with the results obtained from animal studies, in which AVP was shown to promote disruption of the BBB, exacerbate cerebral edema, and augment the loss of neural tissue in various forms of brain injury (e.g., Vakili et al, 2005;Szmydynger-Chodobska et al, 2010). Brain injury has also been shown to result in a substantial increase in the expression of the V 1a receptor (AVPR1A) on cortical astrocytes and on the cerebrovascular endothelium (Szmydynger-Chodobska et al, 2004), suggesting that these two types of parenchymal cells are the primary targets for AVP in the injured brain.…”
Section: Introductionsupporting
confidence: 89%
“…These clinical observations are consistent with the results obtained from animal studies, in which AVP was shown to promote disruption of the BBB, exacerbate cerebral edema, and augment the loss of neural tissue in various forms of brain injury (e.g., Vakili et al, 2005;Szmydynger-Chodobska et al, 2010). Brain injury has also been shown to result in a substantial increase in the expression of the V 1a receptor (AVPR1A) on cortical astrocytes and on the cerebrovascular endothelium (Szmydynger-Chodobska et al, 2004), suggesting that these two types of parenchymal cells are the primary targets for AVP in the injured brain.…”
Section: Introductionsupporting
confidence: 89%
“…21,[24][25][26] Previous work demonstrating that vasopressin may induce brain edema 20,21,56 is supported by multiple studies showing that edema is abolished by blocking the V1aR receptors. [24][25][26][27][28][29] The present results demonstrate that V1aR inhibition accelerates the recovery of [Na + ] e supporting its potential to blunt the ionic dysfunction that leads to edematous changes. Taken together, out findings suggest that SR49059 and other V1aR inhibitors may have potential as therapeutic agents for treating cellular edema by both speeding post-injury ionic recovery and reducing injury-induced elevation of ICP following CCI.…”
Section: Beneficial Effects Of V1ar Inhibition By Sr49059mentioning
confidence: 60%
“…Further, experimental models of intracerebral hemorrhage, middle cerebral artery occlusion, ischemia, and cold and traumatic brain injury have demonstrated that V1aR inhibition reduces brain edema. [22][23][24][25][26][27][28][29][30][31] The underlying mechanism of this response has been attributed to either modulation of vasopressin in the brain parenchyma 17 or its interaction with aquaporin-4 (AQP4). AQP4 is the predominant water channel in the brain and has a significant role in the pathophysiology of brain edema.…”
Section: Introductionmentioning
confidence: 99%
“…38 Data from experimental studies imply that AVP plays a role in brain edema formation as blocking of AVP receptors attenuates brain edema in ischemic mice models. 39 Some limitations merit attention. To assess complications, a time-to-event analysis would have been ideal.…”
Section: Discussionmentioning
confidence: 99%